Effects of Alumina Doping on Mechanical and Tribological Properties of Nitrile Butadiene Rubber - Jia, Yangyang; Zhao, Yaohui; Yan, Chengqi; Wang, Guangfei; Xu, Zehua; He, Qiang (Fibers and polymers, 2021)
In this paper, the alumina nitrile rubber was prepared by mechanical blending. The effects of different amount of alumina doping on tensile, tearing and tribological properties of nitrile rubber were studied and analyzed. The results show that the tensile and tear fracture of alumina nitrile rubber is neat, and there are crack propagation and rapid fracture stages, which do not affect the basic fracture mechanism of nitrile rubber. The doping of alumina enhances the matrix strength of nitrile rubber. When 5 g alumina is added, the synergistic load-bearing effect of alumina and nitrile rubber makes the composite have the best wear resistance, and the wear resistance is more obvious at high load and high speed. In friction test, alumina nitrile rubber mainly shows fatigue and adhesive wear.